Binding gel characterization of alkali-activated binders based on palm oil fuel ash (POFA) and fly ash - Nadziri, Nurulhuda; Idawati, Ismail; Sinin, Hamdan (Taylor and Francis Ltd., 2018)
Pastes of palm oil fuel ash (POFA) and fly ash geopolymer activated with sodium hydroxide (NaOH) and combination of NaOH with sodium silicate (Na2SiO3) were prepared and cured at 80 °C for a duration of 7, 28, and 90 days. The hydrated binding gel products were studied on phase, morphology, and bonding characterization. From these analyses, calcium–sodium–silicate–hydrate (C/N–S–H) gel type appear to form in sole POFA binder but at a very low Ca/Si ratio, while sole fly ash geopolymer binder consists of sodium–alumina–silicate–hydrate (N–A–S–H) binding gel product with a significant Na/Si ratio, regardless of activator types. When both precursors were used, a combination of both gel types was formed, however, Fourier transform infrared spectroscopy and energy-dispersive X-ray analyses show that the N–A–S–H gel is a more dominant product in the binder compared to the C/N–S–H gel. © 2017 Informa UK Limited, trading as Taylor & Francis Group.